Peran self-efficacy dalam memoderasi pengaruh fraud pentagon terhadap perilaku kecurangan akademik mahasiswa pendidikan akuntansi Universitas Negeri Semarang - Chintya Hayu Setyaningsih; Dwi Puji Astuti (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study was conducted to investigate the extent to which the dimensions of the Fraud Pentagon contribute to academic cheating behavior among Accounting Education students at Semarang State University, cohort 2022–2023, as well as to examine whether self-efficacy functions as a moderating variable in that relationship. Employing a quantitative survey design, a sample of 184 students was drawn using proportionate random sampling. Data were gathered via an online questionnaire and analyzed through multiple linear regression and Moderated Regression Analysis (MRA). The findings indicate that all five Fraud Pentagon dimensions — namely pressure, opportunity, rationalization, competence, and arrogance — both individually and collectively exert a significant positive influence on students' tendency to engage in academic fraud. In addition, self-efficacy was found to moderate this relationship in a negative direction, thereby attenuating the impact of the Fraud Pentagon dimensions on academic cheating behavior. These results imply that students with higher levels of self-efficacy are better equipped to resist the factors that typically drive academic dishonesty.